2013
DOI: 10.3892/mmr.2013.1490
|View full text |Cite
|
Sign up to set email alerts
|

Association between ezrin protein expression and the prognosis of colorectal adenocarcinoma

Abstract: Ezrin is involved in maintaining cell structure and cell motility. Expression levels of the ezrin gene correlate with numerous human malignancies. The aim of this study was to explore the role of ezrin in tumor progression and the prognostic evaluation of colorectal adenocarcinoma (CRA). The levels of ezrin protein in 186 CRA samples were evaluated using immunohistochemistry. Furthermore, the correlation between the expression of ezrin and the clinicopathological features of CRA was evaluated with the χ2 and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
3
12
2
1
Order By: Relevance
“…Similar result was obtained by Wang et al, (2009) and Patara et al, (2011). Against this finding, Lin and Chen, (2013) and Fathi et al, (2017) reported that no significant relationship was found between ezrin expression and degree of differentiation of colorectal carcinoma in their studied cases. This may be attributed to different sample size.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similar result was obtained by Wang et al, (2009) and Patara et al, (2011). Against this finding, Lin and Chen, (2013) and Fathi et al, (2017) reported that no significant relationship was found between ezrin expression and degree of differentiation of colorectal carcinoma in their studied cases. This may be attributed to different sample size.…”
Section: Discussionsupporting
confidence: 80%
“…The overall score was expressed as the sum of the intensity and the percentage scores with the product ranging from 0-7. On the bases of the final score, expression was categorized as negative (0-1), weakly positive (2-4) and strongly positive (5-7) (Lin and Chen, 2013).…”
Section: Evaluatin Of Ezrin Expressionmentioning
confidence: 99%
“…The sum of staining intensity and the staining extent scores was used as final staining score. The specimens were divided into three groups according to their scores: 0–1, negative (−); 2–4, weakly positive (+); and 5–7, strongly positive (++) .…”
Section: Methodsmentioning
confidence: 99%
“…Non-expression of ezrin has been more commonly observed in colorectal adenocarcinoma with poor prognostic factors, leading to late-stage tumours and short survival times. 25 Negative or weak ezrin expression in serous ovarian and urothelial bladder has also been reported, and correlated with poor patient outcome. 14,17,18 Similarly, we have shown that, in CCAs, non-expression or low expression of ezrin is more frequently observed in peripheral CCA than in perihilar CCA.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, decreased or no expression of ezrin has been reported in several tumours. Non‐expression of ezrin has been more commonly observed in colorectal adenocarcinoma with poor prognostic factors, leading to late‐stage tumours and short survival times . Negative or weak ezrin expression in serous ovarian and urothelial bladder has also been reported, and correlated with poor patient outcome .…”
Section: Discussionmentioning
confidence: 99%